2016
DOI: 10.1007/s00292-016-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Onkozytom versus chromophobes Nierenkarzinom

Abstract: The differentiation of oncocytic tumors of the kidneys is often difficult, particularly in renal biopsies. Differential diagnoses are chromophobe renal cell carcinoma (ChRCC), renal oncocytoma (RO), the oncocytic variant of papillary renal cell carcinoma (OPRCC), the eosinophilic variant of clear cell renal cell carcinoma (CCRCC) and hybrid oncocytic chromophobe tumors (HOCT). In difficult cases that cannot be resolved by morphology alone, immunohistochemistry is usually helpful. The RO and ChRCC show positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Today, it is clear that the amount and staining pattern of CK7 positive cells is important for the interpretation of CK7. Some authors even suggested to designate CK7 as negative, even when up to 10% of cells express weakly CK7 35 . Other authors state that < 5% CK7 expression is most suggestive of oncocytoma while a negative CK7 staining result is less uniformly considered supportive 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is clear that the amount and staining pattern of CK7 positive cells is important for the interpretation of CK7. Some authors even suggested to designate CK7 as negative, even when up to 10% of cells express weakly CK7 35 . Other authors state that < 5% CK7 expression is most suggestive of oncocytoma while a negative CK7 staining result is less uniformly considered supportive 3 .…”
Section: Discussionmentioning
confidence: 99%
“…119 Yet words and images could not do justice to this experience, Lüders explained: "The cheers of the crowd, the smoke of the hundreds of chimneys, the choirs aboard several ships, the fluttering pennants, the rough Elbe, all of this developed into an impression that no participant will forget." 120 Twenty-year-old Harry Graf Kessler watched the emperor from the deck of a steamer next to the railway bridge. As he noted in his diary, Wilhelm II "came at about two; he stood on the captain's deck with Moltke, looking very straight and well, and a number of other officials; the sight of the crowd of launches and steamers on the Elbe, the crowd of people on the shore, the sea of heads, the deafening hurrahs, was most grand.…”
mentioning
confidence: 99%